Effects of structured self growth exercises on the self-concept of students - Jarapan, Nieva A. Malacat 1952- (1983)
This study was specifically designed to investigate the effects of structured self-growth exercises on the self-concept of the fourth year students in Ilaya Barangay High School. The study used the pretest-posttest control group design. The Pasao Self-Concept Rating Scale was used to measure self-concept. It was recommended that group experiences such as the structured self-growth exercises be utilized during homeroom guidance periods and that this study be replicated in other school settings for greater generalizability of the findings.
Mimeographed.
Thesis (M.Ed.)--University of the Philippines, Diliman.
Vita.
Keywords: Self-perception.